Design and control of actively prestressed compliant mechanisms for variable stiffness actuators. (November 2022) - Mauser, Kristian; Sjarov, Martin; Nowak, Alexander; Campanile, Lucio Flavio; Hasse, Alexander
The paper deals with compliant mechanisms with variable stiffness behavior. Mechanisms with such behavior have received increasing attention in recent years, especially in the context of variable stiffness actuators. In the work presented here, variable stiffness behavior is achieved by targeted application of prestressing forces. An efficient optimization-based method based on linear programming is presented to identify suitable force application points, force magnitudes, and -directions. The performance of the method is numerically and experimentally demonstrated on a compliant mechanism with one translational degree of freedom. The demonstrator is appropriate for application in the research field of variable stiffness actuators. In the experimental investigation, particular emphasis is given on a tailored force-displacement characteristic of the mechanism. The required prestressing forces are realized by a pneumatic artificial muscle. Its modeling and precise control is discussed in detail within the experimental part of the paper. Both the results of the numerical and the experimental investigation demonstrate the potential for precise variation of the stiffness behavior with the presented approach.